Leadership when the heat's on - Cox, Danny; Hoover, John (New York : McGraw Hill Education, 1976)
Aimed at managers who need to learn how to get the most out of their own leadership potential and foster the kind of teamwork and employee spirit needed in today's business world.
The Leader on the Hot Seat -- Good Old Ticky -- The Heat -- A Working Definition of Leadership -- Leading Is an Art -- The Myth of the Natural-Born Leader -- A 79,000-Horsepower Mistake -- The Sonic Boom Salesperson -- Strike Two -- The Turning Point -- 1 Went to Work on Me -- Leadership Is Not Manipulation -- Blowing the Lid Off -- Good versus Best -- An Envelope for Everyone -- Making More than Dad -- The Fork in the Road -- The Problem with Problems -- You Don't Know Me -- Making Definitions Relevant -- Chapter One Closure -- The Emerging Leader Process -- Cultivating a High Standard of Personal Ethics -- High Energy -- Working Priorities -- Having Courage -- Working Hard with Commitment and Dedication -- Going with the Urge to Create -- Getting Goal-Oriented -- Maintaining a Constant Enthusiasm -- Staying Level-Headed -- Helping Others to Grow -- Chapter Two Closure -- The 1st Step--Team Building When the Heat's On -- Rising above the Pettiness -- View from the Shoulder -- Fostering a Genuine and Generous Exchange of Regard -- How Not to Fan the Up Pressure Flames -- Turning Down the Down Pressure Heat -- Contrasting Definitions of Leadership -- Is the Manager Happy? -- All Eyes Are on You -- The Horizontal Advantage -- Three Characteristics of an Effective Organization -- Building Blocks of an Effective Organization -- A Challenge for You -- Three Steps to Growing as a Leader -- Who to Hire -- A Laundry List of Strengths -- Recruiting Made Easy -- Lean on Me -- Motivating the Team
Keywords: LEADERSHIP